Pengaruh Motivasi dan Kerjasama Tim terhadap Kinerja Karyawan Super Indo Puri Depok Mas - Nadia Azahra; Taat Kuspriyono; Yunidyawati Azlina (Yayasan Literasi Sains Indonesia, 2025)
This study was conducted in 2025 using an associative quantitative approach, data collection methods through observation, questionnaires, documentation, and literature studies. The study population included all employees of Super Indo Puri Depok Mas, with a sample size of 40 respondents using a saturated sampling technique. Data analysis was carried out with the help of Statistical Package For The Social Sciences (SPSS) software version 26. The results of the study indicate that motivation has a significant partial influence on employee performance, as indicated by the t-test with a calculated t value of 7,617 > t table 2,206. Teamwork is also proven to have a significant partial influence on employee performance, with a calculated t value of 8.523 > t table 2,206 having a significant value (0.000 <0.05). The variables of motivation (X1) and teamwork (X2) together contribute to the employee performance variable (Y) obtained by 81.1% while the remaining 18,9% is influenced by other factors not included in this study. The results of this study can be used as evaluation material and consideration for companies, to improve strategies to strengthen high motivation and build solid teamwork to improve employee performance.